Intergenerational Mobility and Credit - John Carter Braxton; Nisha Chikhale; Kyle Herkenhoff; Gordon Phillips (Institute of Labor Economics (IZA), 2024)
We combine the Decennial Census, credit reports, and administrative earnings to create the first panel dataset linking parent's credit access to the labor market outcomes of children in the U.S.We find that a 10% increase in parent's unused revolving credit during their children's adolescence (13 to 18 years old) is associated with 0.28% to 0.37% greater labor earnings of their children during early adulthood (25 to 30 years old). Using these empirical elasticities, we estimate a dynastic, defaultable debt model to examine how the democratization of credit since the 1970s – modeled as both greater credit limits and more lenient bankruptcy – affected intergenerational mobility. Surprisingly, we find that the democratization of credit led to less intergenerational mobility and greater inequality. Two offsetting forces underlie this result: (1) greater credit limits raise mobility by facilitating borrowing and investment among low-income households; (2) however, more lenient bankruptcy policy lowers mobility since low-income households dissave, hit their constraints more often, and reduce investments in their children. Quantitatively, the democratization of credit is dominated by more lenient bankruptcy policy and so mobility declines between the 1970s and 2000s.
Keywords: D14; E21; E24; G51; J62; 330; credit limits; bankruptcy; intergenerational mobility